Hiding Secret Text inside a Dynamic Handwritten Signature as Steganography Application - Fahad Layth Malallah; Ayad Hussain Abdalqadir; Mohammad Aldabbagh; Ammar Waisy (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
One of the defects with Cryptography is that, when an opponent sees the message in the encrypted form, they might suspect that the message might carry something important, therefore, they will try to roll back the encrypted form to its original one by using all possible methods. The target of this paper is securing text inside an online handwritten signature in order not to raise any suspicion coming from the attacker. This type of protection named Steganography, which is hiding media inside another media. Here, Least Significant Bit (LSB) method is used. The hosted media is online signature that is consisting of three time series trajectories as: x[t], y[t] and the pen pressure p[t]. The result has shown that the hidden secret message in the source party has been reconstructed successfully with the same secret message in the destination party with a recognition rate is 100%. However, the drawback of this method is a slight distortion to the stego-signature, and hides fewer texts than other media.